Factors Associated to the Incidence of Anemia Among Adolescent Girls in Muaragembong District Bekasi Regency - Fitriyanti, Nisa; Achadi, Anhari (Journal of Public Health for Tropical and Coastal Region, 2024)
AbstractIntroduction: Anemia is still a major health problem among adolescent girls. The prevalence of anemia among adolescent girls in Muaragembong District Bekasi Regency in 2022  reached 68.7%, so Muaragembong Health Center triggered intervention through innovation programs in iron supplements. This study aimed to analyze factors related to the incidence of anemia among adolescent girls in Muaragembong District Bekasi Regency.Methods: This was a quantitative study with a cross-sectional study design. The subjects were 150 adolescent girls of grade XII from 5 schools in Muaragembong District. The sampling method used was probability sampling with clustered random sampling technique. Hemoglobin (Hb) levels was measured by Hemocue Hb meter device. Data on food consumptions were collected through Food Frequency Questionnaires (FFQ). Data analysis was conducted through Chi square tests.Results: Based on the results, 26% of adolescent girls sufferred from anemia. The factors of  anemia incidence were thin nutritional status (p=0.0001), abnormal menstrual patterns (p=0.0001), non hand-washing behavior (0.016), unbalanced food consumption patterns (p=0.002), and iron supplement consumption <4x/ month (p=0.0001). The results of multiple logistic regression tests showed that abnormal menstrual patterns (OR=22.07; 95% CI: 3.24-150.51), iron supplement consumption<4times/mo (OR=10.83, 95% CI: 1.30-89.88), thin nutritional status (OR=4.23, 95%CI: 1.44-12.40), and balanced food consumption patterns (OR=0.27, 95% CI: 0.09-0.84) were related to the incidence of anemia in adolescent girls.Conclusion: The dominant factor of anemia in adolescent girls was abnormal menstrual pattern. However, other factors: iron supplement consumption and balanced food consumptions were also important factors related to anemia.